The diversity of trends, experiences and approaches in electronic publishing : evidences of a paradigm shift on communication - Costa, Sely Maria de Souza (2003)
Electronic publishing constitutes one of the most exciting themes nowadays, amongst academics, at least, though substantial effects of IT usage for communication purposes in other than academic sceneries have also set off enthusiasm on people involved with that. Within the academic environment the use of IT for communicating research by scientists and scholars from different bodies of knowledge has brought about significant changes in the scholarly communication process, particularly in journal production and distribution, conference organisation and a number of other actions regarding making knowledge public. Alternatively, the use of IT within business and technological environments has also triggered changes concerning their stakeholders’ interactions. As a consequence, significant changes in communication have been observed, much of them clearly identified in the works submitted to and presented at ElPub2003. a quick glance at ElPub proceedings from 1997 to 2002 allow to observe the evolution of such an It is important to note that changes are also an important and stimulating theme in whatever context. In the academic environment, changes have been approached by Kuhn as either giving birth to new paradigms or being born from them. In fact, Kuhn (1970), Meadows (1998), Pahre (1996) and others have approached paradigm as something very important in the academic world, as it constitutes a conceptual framework involving both theory and practice, and providing guidance on what problems deserve investigation and how they should be tackled. In this sense, this speech aims to highlight the major issues under Elpub2003 authors’ concerns, and the way they have been both looked at and dealt with.